2018
DOI: 10.1002/jcu.22581
|View full text |Cite
|
Sign up to set email alerts
|

How much can synthetic cannabinoid damage the heart? A case of cardiogenic shock following resistant ventricular fibrillation after synthetic cannabinoid use

Abstract: New substances are constantly being added to the content of synthetic cannabinoids (SCs). SCs can affect the cardiovascular system and cause hypotension and bradycardia, myocardial infarction, atrial fibrillation, prolonged QTc, and Mobitz type II atrioventricular block. However, no cases associated with ventricular fibrillation (VF) have been reported to date. We report a case of a 26-year-old male patient admitted to the emergency department due to altered consciousness after SC use and requiring prolonged c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Although a case of ventricular fibrillation associated with SC use has been reported, the underlying etiology could not be fully explained. [ 14 ] The different QRS width and T-wave amplitude in our patient group compared to the control group suggest that an arrhythmia risk may associated with SC. It has been suggested in previously reported cases that SCs are capable of causing prolonged QTc and Mobitz type II block.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although a case of ventricular fibrillation associated with SC use has been reported, the underlying etiology could not be fully explained. [ 14 ] The different QRS width and T-wave amplitude in our patient group compared to the control group suggest that an arrhythmia risk may associated with SC. It has been suggested in previously reported cases that SCs are capable of causing prolonged QTc and Mobitz type II block.…”
Section: Discussionmentioning
confidence: 89%
“…Case reports of myocardial infarction,[ 10 ] prolonged corrected QT interval (QTc), and Mobitz type II atrioventricular block[ 13 ] and ventricular fibrillation[ 13 14 ] depending on the use of SCs were earlier reported. Our review of the literature revealed rare clinical studies,[ 15 ] other than case reports, examining the effect of SCs on the cardiovascular system (CVS), a widespread health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Синтетичні канабіоїди здатні викликати субклінічну дисфункцію лівого шлуночка [30], гіпотензію та брадикардію, інфаркт міокарда, передсердну фі- Науковий огляд / Scientific Review бриляцію, подовження інтервалу Q-T, атріовентрикулярну блокаду Мобіц-2. Також було повідомлено про випадок кардіогенного шоку внаслідок фібриляції шлуночків, пацієнт потребував пролонгованої ресусцитації [31]. Ризик розвитку раптової серцевої смерті зростає в п'ятикратному розмірі при споживанні канабісу навіть протягом години, ніж у пацієнтів, які не вживали канабіс.…”
Section: науковий огляд / Scientific Reviewunclassified
“…N-methyl-2,3-dihydro-1H-inden-2-amine Benzofurans and benzodifurans or arylalkylamines [31][32][33]. Tachycardia was reported in 76% of 33 SCs-intoxicated patients in Italy [34].…”
Section: Epidemiologymentioning
confidence: 99%